Struggling in the Shadows. A Legal History of Female Labor in Italy Between the Liberal Age and Fascism (Italian Review of Legal History, 2024)
Law and its history play a significant role in supporting the thesis concerning the unequal treatment experienced by women.The patriarchal conception of infirmitas sexus and the dichotomy between the ‘male breadwinner’ archetype and the ‘female caregiver’ role have profoundly shaped Western societies, regulating the spaces and societal roles allocated to women, including the realm of female labor.In recent times, there has been a noteworthy resurgence of interest in comprehending the legal condition and subjective status of female workers. This renewed attention can be attributed to the proliferation of historical-legal research on women’s employment, which has meticulously documented the legal mechanisms employed to regulate the socio-economic dynamics governing labor practices.In the context of understanding how law influenced the subjective status of female workers, it’s crucial to focus on the period from Italian national unification to the fascist dictatorship (mid-19th century to mid-20th century). To achieve this, the present study examines the intersection between normative, doctrinal, and jurisprudential aspects, tracing the main historical paths from the heyday (§ 2) through the crisis of the liberal era (§ 3), to the fascist totalitarianism (§ 4).The thesis to be asserted is that, despite the enduring stereotype of female marginalization, emerging operational patterns marked a significant shift in the legal structures of gender inequality, reflecting the interplay of new legal elements alongside changes in state organization and power dynamics.Between the mid-19th century and the early 20th century, a deliberate legal strategy resulted in the obscurity of female workers.Women of means found themselves in a state of ambiguity, receiving treatment oscillating between exclusion and protection policies. This was achieved through the implementation of distinctive subjective treatments, which were sanctioned by diminished legal rights.Conversely, impoverished female workers were denied significant legal standing, with market forces and industrialists assuming the authority to entirely dictate the terms of engagement. The adverse conditions faced by working-class women persisted despite the legislative interventions targeting female labor, such as the so-called Weaker Forces laws enacted between 1902 and 1909. These laws aimed to safeguard the reproductive health of female workers, revealing a pervasive disregard for the material realities of working conditions. This indifference is evidenced by official reports, widespread violations ofregulations, and a judiciary that primarily focused on enforcing existing laws rather thanaddressing systemic issues.The mid 1910s-mid1920s transition from a liberal state to dictatorship was characterized by the subjugation of female labor to the imperatives of maintaining public order and bolstering national production. Amidst the political upheaval at the turn of the century, public interests were invoked to manage crises, such as widespread strikes, leading to an expansion of the executive power through mechanisms of delegated decree authority.Despite women making inroads into traditionally male-dominated sectors like public administration and education, the enactment of executive decrees disregarded the rule of democracy. This served to justify the suspension of regulations protecting women such as the prohibition of night work, minimum hiring standards, and maximum shift durations in the name of collective interests.The curtailment of female workers’ rights through legally binding measures for exceptional circumstances escalated during World War I. Emergency decrees offered women temporary employment opportunities, which abruptly ceased with the conclusion of hostilities, resulting in mass layoffs to accommodate returning male workers. Judicial authorities also echoed the notion that female labor’s public nature should prioritizethe collective interest in maintaining production efficiency, often at the expense of safeguarding female workers’ rights.Fascism, finally, drew on the burst of public law in previous years to integrate individuals into a broader entity—the State—wherein the family served as the original nucleus and a vital instrument for demographic expansion. Women bore the brunt of this organic conception of the social order, being relegated to the singular role of motherhood. This ideological stance reveals the core principles guiding legislation on female labor duringthe Fascist era: the restriction of women’s involvement in non-domestic labor spheres, except in the cases where their engagement outside the home was necessary.The regime’s endeavor to convert employed women into homemakers became evident through the reforms of 1934, which rendered women’s labor less attractive to employers and favored the hiring of men. This strategy aimed to reconcile the imperatives of a crisisprone labor market and economy with the regime’s demographic and ideological goals.The judiciary further affirmed the hostility toward female labor, providing differential treatment on whether women chose to return to domestic roles or pursued employment and career advancement. Despite embracing a new framework, fascism intercepted the trajectory set forth by liberal and late-liberal ages, i.e., the choice of an obscure legal status, preferably concentrated within the domestic walls to be reserved for the female worker. Female workers found themselves subjected to treatment oscillating between normative ‘aphasia’ and theapplication of exceptional regulations, all in pursuit of public and collective interests. The absence of laws and the reluctance to enforce existing ones, along with conservative judicial practices and directives, illustrate that the disjunction between theoretical principles and practical realities did not constitute a contradiction. Instead, it clearly depicted the status of female labor amidst the transition from the liberal age to fascism.With the onset of the republican era, the paradigms of female invisibility and concealment gave way to a legal framework characterized by the prioritization of individual rights. This shift marked a newfound female visibility acknowledged by the law, particularly within the realm of employment. Even today, however, persisting gender disparities and unfavorable working conditions underscore the substantial challenges that women, particularly working mothers, continue to face in balancing work and family responsibilities. It is not the role of legal history to offer solutions. Nevertheless, the historical analysis of legal phenomena can provide gender studies with a reflective lens to contextualize present-day issues surrounding female labor.By tracing the connections and evaluating the operational strategies experimented to perpetuate unequal treatment, this approach helps frame contemporary challenges within a broader historical continuum. Among the legal mechanisms devised to perpetuate gender inequality in the labor sphere, the period spanning from the liberal age to fascism stands out as a particularly fertile. It exhibited a remarkable capacity to innovate and adapt, offering novel solutions to emergent circumstances.
Keywords: female labor; exploitation and inequalities; cultural legacies, law, and governance of society; legal history and gender history; contemporary era.